Transfersome as Topical Drug Delivery: Formulation and Characterization: Transfersome sebagai Pengiriman Obat Topikal: Formulasi dan Karakterisasi - Nur Zakiyah Darajat; Anis Chaerunisaa; Marline Abdassah (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2023)
A transdermal delivery system is a non-invasive delivery system that provide a controlled therapeutic effect. However, this system has a barrier that is the outermost layer of the skin, so that only part of the drug can be administered via the transdermal route. The use of the vesicular system as a carrier for drugs or active substances is a solution for transdermal delivery systems to be able to pass through the skin barrier. One of the vesicular systems that can overcome this problem is transfersome. Displacement is elastic and can change shape by squeezing itself to pass through smaller-than-sized pores. In addition, transfersomes can encapsulate drugs or active substances that are amphiphilic, and have permeation ability than conventional liposomes. This review article aims to explain the definition and general description of transfersomes, their mechanism of action, methods of preparation and characterization, and their recent application in drug delivery using the vesicular transfersome system.